The Maranaws - Gibb, Hugh. ([Manila] Felta Book Sales, 1981)
A short documentary on the customs, traditions, religion and cultural life of the Maranaws.
VHS.
Keywords: Muslims -- Philippines; Minorities; Ethnic group; Philippine history